IMPROVED LEARNING OUTCOMES IN CALCULATING REDUCTION OPERATIONS USING CONCRETE OBJECT MEDIA - Suheryani, Yani; Indriani, Susi; Murni, Sukma (IKIP Siliwangi, 2018)
This research is motivated by the low understanding of grade 1 students on calculating operating material reduction. Through observation, it is known that the students' low understanding of the calculation counting reduction material is a difficult subject to understand. The most easily found indications are pesetas students' learning outcomes which tend to be less satisfactory, especially in obtaining average scores under other lessons. From the observations of the author of grade 1 students of SDN 009 Cikadut, Mandalajati Subdistrict, Bandung City, experienced difficulties in the reduction, the teacher factor also became a problem of how teachers optimize learning planning to improve grade 1 students' understanding of calculating reduction operations. This study aims to obtain an overview of learning planning in the calculation of reduction operating material by using concrete object media so as to obtain an improvement in the learning process of mathematics in grade 1 students of 009 Cikadut Public Elementary School and find out the results of the students' values in calculating the reduction of operational material using concrete objects. Looking at the situation in the field, the researchers are interested in doing research using concrete objects so that they are expected to trigger activity and creativity in the teaching and learning process that is not only teacher-dominated.